How long can the term of office of the Polish parliament last? A legal-constitutional analysis - Litwin, Tomasz (Przegląd Politologiczny, 2018)
The main research aim of this article is an analysis of the length of the parliamentary term of office in Poland based on the analysis of legal rules. According to the art. 98 para. 1 of the Constitution, the parliamentary term of office starts on the day on which the Sejm assembles for its first sitting and ends on the day preceding the first assembly of the newly elected Sejm. Although the mentioned rule also expressly states that parliamentary term of office lasts 4 years, the length of the particular terms of office could be very different. If the parliamentary term of office is shortened, it could last even less than two months. If it is prolongated because of the introduction of the extraordinary measure, it could last approx. 5 years (in case of emergency state), or it maximal length can not be defined. Moreover, even in case of the “normal” terms of office they could have different length – slightly less than 4 years or longer than 4 years by even a few weeks. The presented considerations lead to the conclusion that there is need to make certain amendments of the rules of law concerning this area, which would ensure minimal 4 years length of the “normal” parliamentary term and regulate the organisation of the parliamentary elections after the termination of the extraordinary measure. Author analysed the legal rules basing on legal-dogmatic method and interpreted them by using such methods of their interpretation as: language-logical, teleological and systematic.